Scenarios for the Application of Virtual Water in the Local Governance of Isfahan Province with a Future Research Approach - Afshin Mottaghi; Mohammad Yosefi Shatori; Arash Ghorbani Sepehr (آب و توسعه پایدار)
Isfahan Province is located in the arid and semi-arid region of Iran and is considered one of the country's leaders in the production and export of agricultural and industrial products. These characteristics have created challenges for local governance in this province. In the current research, the upcoming scenarios in the field of virtual water application in the local governance of Isfahan province have been investigated using a future research approach. This research is descriptive-analytical, and data were collected through library and field methods and analyzed using Micmac, Scenario Wizard, and Vensim software. The results of the research showed that coordination between various institutions and stakeholders, management of water resources in the agricultural sector in line with other sectors, the collective interest approach, development of water-intensive industries, climate change, rainfall patterns, and population size are among the key variables affecting the use of virtual water in local governance of Isfahan province. In the analysis of key drivers and possible scenarios, the output of the Scenario Wizard software showed that out of the 18 situations on the scenario page, the largest number of situations are related to scenarios that put the local governance of Isfahan province on a crisis path. These situations comprise 38.88 percent of the total situations on the scenario page. Therefore, the future situation of virtual water use in Isfahan province was assessed as critical.